Transcription Factor C/EBP Homologous Protein in Health and Diseases - Yang, Yuan; Liu, Lian; Naik, Ishan; Braunstein, Zachary; Zhong, Jixin; Ren, Boxu (Frontiers in Immunology, 2017)
C/EBP homologous protein (CHOP), known also as DNA damage inducible transcript 3 (DDIT3) and as growth arrest & DNA damage inducible protein 153 (GADD153), is induced in response to certain stressors. CHOP is universally acknowledged as a main conduit to ER stress-induced apoptosis. Ongoing research established the existence of CHOP-mediated apoptosis signaling networks, for which novel downstream targets are still being determined. However, there are studies that contradict this notion and assert that apoptosis is not the only mechanism by which CHOP plays in the development of pathologies. In this review, insights into the roles of CHOP in pathophysiology are summarized at the molecular and cellular levels. We further focus on the newest advances that implicate CHOP in human diseases including cancer, diabetes, neurodegenerative disorders, and notably, fibrosis.